Evaluation and Analysis of Typical Disease Risk Matrix of Concrete Slab Beam Bridge. Issue 3 (February 2019) - Gu, Wan; Kang, Aihong; Xiao, Peng; Fan, Zhao; Mao, Quan
Abstract: In view of the current technical status assessment of concrete slab beam bridge, the problem of the disease severity can not be objectively and accurately reflected. This paper takes the typical disease of the concrete slab bridge as the research object to carry out the risk matrix evaluation. In order to eliminate the risk matrix in the risk matrix, we introduce the Borda order value method to establish a qualitative and quantitative comprehensive risk assessment model.On this basis, based on the analytic hierarchy process (AHP), the weight of risk factors is calculated to form a typical disease risk assessment system of plate girder bridge, which can reduce the influence of subjective factors in the bridge technical evaluation process.